Professionalization of Civil Service in Hungary: The Potential Impacts of Centralizing Public Administration Education - Márton Gellén (Central European Public Administration Review)
The article examines the recent developments in public administration training in Hungary and draws conclusions for the future. The paper analyzes the connection between legalism and professionalism in Hungary. Legalism and professionalism are displayed as contrary notion by a considerable number of theorists. It appears that »legalism« is an appropriate label for the past status of public administration that reformists long to abandon. Since Hungary is considered to be part of the legalistic culture of European public administration (PA), the assumed conflict between legalism and professionalism appears more vividly. As part of the currently undergoing reform, professionalism received an influential institutional promoter within the Hungarian PA: the National University of Public Administration that is primarily a university but is also a successor of the government agency that used to be in charge of civil service professional training. The article concludes with summarizing the currently undergoing reform regarding professionalism that is also presented as being contrary to the legalistic PA in the government reform program for modernizing PA.